ENGLISH TEACHERS’ PERCEPTIONS OF DIAGNOSTIC ASSESSMENT IMPLEMENTATION UNDER THE MERDEKA CURRICULUM - Ayuaneka, Debi (Fakultas Keguruan Ilmu Pendidikan Universitas Ibn Khaldun Bogor, 2026)
The implementation of the Merdeka Curriculum in Indonesia emphasises flexible, student-centred, and differentiated learning, where diagnostic assessment plays a key role in identifying students’ readiness and learning needs. In English Language Teaching (ELT), this is particularly important due to variations in students’ language proficiency and backgrounds. This study aims to examine English teachers’ perceptions of the purpose, role, and challenges of implementing diagnostic assessment at SMK Negeri 3 Lahat. A mixed-methods approach with a convergent design was employed, involving five English teachers selected through purposive sampling. Data were collected through questionnaires and semi-structured interviews and analysed using descriptive statistics and thematic analysis. The findings reveal that teachers generally hold positive perceptions of diagnostic assessment and recognise its importance in supporting differentiated learning and identifying students’ starting points. However, several challenges were identified, including limited time, insufficient training, lack of clear guidelines, and inconsistent implementation. These findings suggest that while diagnostic assessment is well-aligned with the principles of the Merdeka Curriculum, its effective implementation requires stronger institutional support, clearer guidelines, and continuous professional development for teachers.